Cardiorespiratory and metabolic consequences of detraining in endurance athletes - Barbieri, Arianna; Fuk, Andrea; Gallo, Gabriele; Gotti, Daniel; Meloni, Andrea; La Torre, Antonio; Filipas, Luca; Codella, Roberto (Frontiers in Physiology, 2024)
Background: A training program can stimulate physiological, anatomical, and performance adaptations, but these improvements can be partially or entirely reversed due to the cessation of habitual physical activity resulting from illness, injury, or other influencing factors.Purpose: To investigate the effects of detraining on cardiorespiratory, metabolic, hormonal, muscular adaptations, as well as short-term and long-term performance changes in endurance athletes.Methods: Eligible studies were sourced from databases and the library up until July 2023.Included studies considered endurance athletes as subjects and reported on detraining duration.Results: Total cessation of training leads to a decrease in VO2max due to reductions in both blood and plasma volume. Cardiac changes include decreases in left ventricular mass, size, and thickness, along with an increase in heart rate and blood pressure, ultimately resulting in reduced cardiac output and impaired performance. Metabolically, there are declines in lactate threshold and muscle glycogen, increased body weight, altered respiratory exchange ratio, and changes in power parameters. In the short term, there is a decrease in insulin sensitivity, while glucagon, growth hormone, and cortisol levels remain unchanged. Skeletal muscle experiences reductions in arterial-venous oxygen difference and glucose transporter-4. Implementing a partial reduction in training may help mitigate drastic losses in physiological and performance parameters, a consideration when transitioning between training seasons.There is a dearth of data investigating the detraining effects of training reduction/cessation among endurance athletes. Delving deeper into this topic may be useful for professionals and researchers to identify the optimal strategies to minimize these effects.